Design de aços inoxidáveis austeníticos de alto teor de nitrogênio via triagem de alto desempenho por método CALPHAD - Ferreira, Victor Hugo Mafra Monfredo (2023)
Nickel is essential for austenitic stainless steels of the 3xx class (8-10 wt%) due to its austenitizing character. However, its notorious price volatility directly affects the stainless steel industry. In light of this, there is a need to develop stainless steels that partially replace nickel with other austenitizing elements. The aim of this work was to develop compositions of austenitic stainless steels with a high N content using computational methods. Computational tools based on the CALPHAD method were employed to select a composition based on predefined criteria (composition, phases present, % N, cost, and PREN). The alloy's microstructure was analyzed through optical and scanning electron microscopy, while the phases present were identified through X-ray diffraction. The chemical composition was determined using spark emission spectroscopy; elements C, S, N, and O were analyzed by combustion and quantified by infrared absorption. Mechanical properties were evaluated according to ASTM E8/E8M-11 standards. Pitting corrosion resistance was assessed through cyclic potentiodynamic polarization in 3.5 wt% NaCl, and sensitization was evaluated following ISO 12732; susceptibility to intergranular corrosion was determined according to ASTM A262-15 Practice A. Electrochemical impedance spectroscopy tests were also conducted as a complement. After high-performance screening, manual modifications were made to the compositions to improve nitrogen solubility. The results demonstrated that the developed alloys exhibited an austenitic microstructure with the presence of AlN, reducing the nitrogen content in solid solution. The mechanical properties of the alloy surpassed those of AISI 201 steel. However, due to the presence of AlN, the corrosion resistance behavior of the alloy was affected. These findings are significant for the development of austenitic stainless steels with a high nitrogen content, aiming to enhance their mechanical properties and corrosion resistance.